An overview of evaluation of low back pain - Mohammed, Farid; Khan, Arshiya; Verma, Vikas; Pandey, Abhishek (International Journal of Research in Medical Sciences, 2017)
Background: Low back pain has plagued humans for thousands of years and it is extremely common with lifetime prevalence of 60-90% and annual incidence of 5% so we studied the problem of acute lumbosciatic syndrome which is defined as pain located near the loins in the lower back region and along the sciatic nerve, its remedies with objective to find out the possible causes of acute lumbosciatic syndrome. Aim of the study was to study characteristics of low back pain patients and outline the best possible treatment for them. Methods: The study comprises of 110 patient of adolescent to elderly age presenting with acute low back pain with radiation of pain to buttock and thigh. The prospective randomized study was completed in two years at the department of orthopedics at a tertiary care center. Results: Acute low backache was found to be more common in upper middle class and Lower class. Medium and heavy manual workers were found to be more predisposed to acute low backache and among specific occupation porters carrying heavy weights were most commonly involved. Prolapsed intervertebral disc was found be commonest cause of acute lumbosciatic syndrome. By conservative treatment in a year there was 76% of patients showed improvement in back pain, 73% showed improvement in paresthesias, 79% showed improvement in numbness and 69% showed improvement in neurological claudication. Education in proper posture and body mechanics is helpful in returning the patient to the usual level of activity after the acute exacerbation has been relieved. Conclusions: Every patient of low back pain should be thoroughly examined on all parameters before reaching to final diagnosis and treatment of low back pain by conservative treatment should be aimed on the prevention rather than treatment by multiple drugs.